Educational Capabilities of physical education teachers and their role in developing inclusive sports talents among students during sports lessons (Damu Journal of Sport Sciences, 2024)
Conducting research that addresses the topic of educational Capabilities of physical education teachers and inclusive sports talents among students during sports lessons is of great importance. Therefore, the research aimed to reveal the nature of the role played by educational Capabilities of physical education teachers in developing inclusive sports talents among students after revealing the extent to which physical education teachers possess educational Capabilities, as well as the extent to which students possess inclusive sports talents. The researcher used the descriptive approach in this research by using both the survey method and the correlation method. The researcher identified physical education teachers in schools affiliated with the Babylon Education Directorate for the academic year (2023-2024) as a community for the current research. The researcher chose from this community physical education teachers in middle schools to form the main research sample, and the sample consists of (245) teachers. In order to obtain the data required in the research, the researcher prepared two measurement tools: the first tool to measure the level of educational Capabilities among physical education teachers with a number of (15) paragraphs, and the second tool to measure the level of inclusive sports talents among students with a number of (15) paragraphs. The paragraphs of the two tools are answered with five-weight . After extracting the results of the final application and processing them statistically, analyzing and discussing them, the researcher concluded a set of conclusions:Physical education teachers in middle schools affiliated with the Babil Education Directorate have educational Capabilities that are characterized by being of an average level in terms of teaching physical education. The students of the preparatory schools affiliated with the Directorate of Education of Babylon have average-level capabilities in terms of inclusive sports talents.- The educational Capabilities possessed by physical education teachers have an important and prominent role in developing the inclusive sports talents of their students.